The life of the Buddha - Maltby, Clive ([Australia : BBC Active, 2003)
Using CGI graphics, expert testimony and the latest archeological findings, this film recreates the life of someone who never wanted to be worshipped as a God, but changed the course of history for man, and the search for eternal peace and happiness
Executive producer, Tessa Livingstone ; camera, Steve Robinson ; edited by Gregers Sall
Narrator: Ali Ballantyne
DVD format
Keywords: Gautama Buddha; Buddhism